The American Venous Forum, American Vein and Lymphatic Society and the Society for Vascular Medicine expert opinion consensus on lymphedema diagnosis and treatment. (May 2022) - Lurie, Fedor; Malgor, Rafael D; Carman, Teresa; Dean, Steven M; Iafrati, Mark D; Khilnani, Neil M; Labropoulos, Nicos; Maldonado, Thomas S.; Mortimer, Peter; O'Donnell, Thomas F; Raffetto, Joseph D; Rockson, Stanley G; et al.
Background: Lymphedema imposes a significant economic and social burden in modern societies. Controversies about its risk factors, diagnosis, and treatment permeate the literature. The goal of this study was to assess experts' opinions on the available literature on lymphedema while following the Delphi methodology. Methods: In December of 2019, the American Venous Forum created a working group tasked to develop a consensus statement regarding current practices for the diagnosis and treatment of lymphedema. A panel of experts was identified by the working group. The working group then compiled a list of clinical questions, risk factors, diagnosis and evaluation, and treatment of lymphedema. Fifteen questions that met the criteria for consensus were included in the list. Using a modified Delphi methodology, six questions that received between 60% and 80% of the votes were included in the list for the second round of analysis. Consensus was reached whenever >70% agreement was achieved. Results: The panel of experts reached consensus that cancer, infection, chronic venous disease, and surgery are risk factors for secondary lymphedema. Consensus was also reached that clinical examination is adequate for diagnosing lymphedema and that all patients with chronic venous insufficiency (C3–C6) should be treated as lymphedema patients. No consensus was reached regarding routine clinical practice use of radionuclide lymphoscintigraphy as a mandatory diagnostic tool. However, the panel came to consensus regarding the importance of quantifying edema in all patients (93.6% in favor). In terms of treatment, consensus was reached favoring the regular use of compression garments to reduce lymphedema progression (89.4% in favor, 10.6% against; mean score of 79), but the use of Velcro devices as the first line of compression therapy did not reach consensus (59.6% in favor vs 40.4% against; total score of 15). There was agreement that sequential pneumatic compression should be considered as adjuvant therapy in the maintenance phase of treatment (91.5% in favor vs. 8.5% against; mean score of 85), but less so in its initial phases (61.7% in favor vs. 38.3% against; mean score of 27). Most of the panel agreed that manual lymphatic drainage should be a mandatory treatment modality (70.2% in favor), but the panel was split in half regarding the proposal that reductive surgery should be considered for patients with failed conservative treatment. Conclusion: This consensus process demonstrated that lymphedema experts agree on the majority of the statements related to risk factors for lymphedema, and the diagnostic workup for lymphedema patients. Less agreement was demonstrated on statements related to treatment of lymphedema. This consensus suggests that variability in lymphedema care is high even among the experts. Developers of future practice guidelines for lymphedema should consider this information, especially in cases of low-level evidence that supports practice patterns with which the majority of experts disagree.